PENGARUH PROMOSI DAN MUTASI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA KANWIL II PT. PEGADAIAN (PERSERO) PEKANBARU - Putri, Adelia Trisna; Hendriani, Susi; Ibrahim, Restu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of promotion and transfer positions to job satisfaction of employees at Kanwil II PT. Pegadaian (Persero) Pekanbaru. The population in this study were all employees who have promotions and transfers in 2013 as many as 74 people, and for the determination of the sample used census method so that the entire population sampled in this study. Analysis of the data used is descriptive analysis and quantitative analysis using multiple linear regression with SPSS version 18.00. The results showed that the variable promotion has significant impact on employee job satisfaction, whereas mutation variable has no significant effect on job satisfaction of employees in Kanwil II PT. Pegadaian (Persero) Pekanbaru.Keywords: promotion, mutation, job satisfaction